EFFECTIVENESS OF HEALTH PROMOTION USING ASSEMBLR EDU ON INCREASING KNOWLEDGE AND ATTITUDE OF MAINTAINING DENTAL AND ORAL HEALTH - Amalia Putri; Riky Hamdani; Isnur Hatta; Rosihan Adhani; Deby Kania Tri Putri (FKG ULM, 2024)
Background: The increase dental and oral health problems in children can be caused by an attitude of neglecting dental and oral hygiene which is based on a lack of knowledge. One example is the low attitude and behavior when brushing teeth and dental visit in Banjarmasin City. Purpose: This study aims To analyze the effectiveness of health promotion using Assemblr Edu on increasing knowledge and attitudes about maintaining oral health in students aged 10-12 years at SDN Kebun Bunga 4 Banjarmasin. Method: This research uses a type of quasy-experimental design with a nonequivalent control group design and uses non-probability sampling technique as purposive sampling. The population is students aged 10-12 years at SDN Kebun Bunga 4 Banjarmasin. The sample consisted of 16 people in the Assemblr Edu group and 16 people in the control group. The instrument used in this research is a questionnaire. Data analysis used Wilcoxon test and Mann Whitney test. Results : The Wilcoxon test showed that there were differences in knowledge and attitudes before and after health promotion in the Assemblr Edu intervention group (knowledge : p=0,000; attitudes : p=0,000), in the control group there was no difference in knowledge and attitudes between pretest and posttest (knowledge : p=0,755; attitudes : p=0,290). The results of the Mann Whitney between the intervention and control groups (knowledge : p=0,000; attitudes : p=0,001). Conclusion: Health promotion using Assemblr Edu is effective in increasing knowledge and attitudes about maintaining oral health.